The Study of Cuneiform in the USSR during the past 30 Years - Djakonov, I. M.
The last § reads: The comparatively small group of Soviet scholars who have laboured in the past 30 years on the study of Cuneiform, has to its account valuable achievements. These achievements give to our Soviet Science the right to occupy in the scientific world the honorable place which it already has.